Presenza di nematodi in gamberi di nassa (Plesionika narval) - GAGLIO, Gabriella; NAPOLI, ETTORE; CAVALLARO, MAURO (Società Italiana di Patologia Ittica, 2016)
Plesionika narval (Fabricius, 1787) is a shrimp, belonging to the family Pandalidae, that lives between 300 and 800 meters deep throughout the Mediterranean area, but you can also find this crustacean at shallower depths. Its meat is very tasty and appreciated that assumes considerable economic importance in the fisheries sector. The aim of this paper is to report the presence of nematodes from the ovary of Tyrrhenian prawn shrimps, Plesionika narval. The shrimps were purchased at a public fisheries on the island of Lipari (Aeolian Islands), A total of one hundred and fifty-two shrimps were inspected (i.e., 38 males and 114 females of witch 92 were gravids); 10 females out of 114 showed each a gravid nematode into the eggs having the characteristic bluish color. By morphometric study and using routinar classification keys, the parasites were found to belong to the genus Trophomera sp. (Rubtsov & Platonova, 1974). The genus Trophomera is a member of Benthimermitidae family consists of uncommon parasitic nematodes of crustaceans and molluscs. In fact, these nematodes have been described as immature forms in shellfish and as adults usually free-living or parasites of bivalve molluscs. The difficulty of finding these nematodes is due to the fact that their habitat is the marine environment of depth. In our knowledge this is the first report of nematodes belonging to the family Benthimermitidae as parasites of Plesionika narval. The presence of parasites "macroscopically visible" offers many ideas on the need to protect consumers and promote more extensive supply chain controls, even for shellfish. RIASSUNTO - Plesionika narval (Fabricius, 1787) è un crostaceo decapode appartenente alla famiglia dei Pandalidae. La specie è presente in tutto il Mediterraneo, maggiormente diffusa nel bacino occidentale. Plesionika narval è un gambero che vive tra i 300 e gli 800 metri di profondità in tutta l'area Mediterranea, ma è possibile ritrovarlo anche a profondità minori. Le sue carni sono particolarmente saporite e ...